Proceedings of the 6th International Accounting Conference (IAC 2017) 2018
DOI: 10.2991/iac-17.2018.6
|View full text |Cite
|
Sign up to set email alerts
|

Critical Success Factors of the Implementation of Knowledge Management at PT XYZ

Abstract: The rapid development of science and technologies can enhance competitiveness between companies. Organizations need to properly use their knowledge to gain competitive advantage. Organizations should implement knowledge management to maximize their knowledge. This study aims to determine the critical success factors of the implementation of knowledge management at PT XYZ. This study was conducted using a quantitative approach and a questionnaire as a research instrument. The data analysis used AMOS 21. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Organisational strategy focus on KM as described by Jennex (2017), deals majorly with aligning KM initiative with organisations competitive strategy as well as identifying knowledge users, knowledge needed, KM metrics and incentives that are needed to ensure the use of knowledge. Aligning with Kunthi et al (2017), Abbaszadeh (2010), top management support is one of the most influential factors in determining the success of KM. Adegbembo (2014), however, found that the support of top management is essential in overcoming the challenges of KM in QSF in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Organisational strategy focus on KM as described by Jennex (2017), deals majorly with aligning KM initiative with organisations competitive strategy as well as identifying knowledge users, knowledge needed, KM metrics and incentives that are needed to ensure the use of knowledge. Aligning with Kunthi et al (2017), Abbaszadeh (2010), top management support is one of the most influential factors in determining the success of KM. Adegbembo (2014), however, found that the support of top management is essential in overcoming the challenges of KM in QSF in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the knowledge sharing process occurs when someone asks a question, and the other party answers. According to Kunthi et al (2018), the benefits of sharing knowledge include saving time and increasing productivity, helping solve work problems, and receiving knowledge about proven solutions. Besides, from the author's point of view, this process can build reputation and self-actualization, maximize knowledge creation, and open opportunities for exploring and creating new knowledge.…”
Section: Knowledge-sharingmentioning
confidence: 99%
“…Knowledge management is influenced by cultural factors such as motivation to share knowledge, management support, trust, and a spirit of teamwork. IT cannot alone achieve effective knowledge sharing in the absence of factors such as trust, culture, organizational climate, and leadership support (Enakire, 2020; Kunthi, Sensuse & Tobing, 2017). In fact, some studies found that systems and technology tools had a detrimental impact on knowledge sharing (Riege 2005).…”
Section: Organisational Cultural and Structural Factorsmentioning
confidence: 99%
“…Studies have shown that individuals avoid sharing knowledge because of the fear of the unknown and also because they felt that they could be demoted or lose their jobs if they shared their skills and expertise (Riege 2005). Important factors of organizational culture are organizational structure, leadership, process, structure, reward system, motivation, trust, interaction, IT system and people (Enakire, 2020; Kunthi, Sensuse & Tobing, 2017;Kim & Ju 2008). Organisational structure consists of rules, policies, procedures and processes, hierarchical levels, departmentalisation of employees and systems of motivational incentives, and coordination of work processes within a firm (Ajanaku & Mutula 2018).…”
Section: Organisational Cultural and Structural Factorsmentioning
confidence: 99%